Automatic routing of flexible 1D components with functional and manufacturing constraints. (October 2016) - Hermansson, T.; Bohlin, R.; Carlson, J.S.; Söderberg, R.
Abstract: This article presents a novel and unifying method for routing of flexible one-dimensional components such as cables, hoses and pipes with geometric design constraints. A deterministic and resolution complete grid search is used to find a nominal configuration of the component that is collision-free and satisfies functional and manufacturing constraints. Local refinement is done in tandem with a computationally efficient and physically accurate simulation model based on Cosserat rod theory to ensure that the deformed configuration still satisfies functional constraints when influenced by gravity. Test results show that the method is able to solve industrial scenarios involving complex geometries and real constraints with different objectives in mere seconds. Highlights: We propose a method for routing of flexible components with design constraints. Deterministic grid search generates feasible and globally optimal nominal solutions. A Cosserat rod model coupled with nonlinear optimization controls elastic deformation. The method is capable of solving industrial scenarios with high detail.